Combinatorial image analysis : 20th International Workshop, IWCIA 2020, Novi Sad, Serbia, July 16-18, 2020, Proceedings /: 20th International Workshop, IWCIA 2020, Novi Sad, Serbia, July 16-18, 2020, Proceedings. (2020) - Unknown
No abstract available